Unstable semiquinone in photosynthetic reaction center - Gerencsér, László; Maróti, Péter (Acta Biologica Szegediensis, 2005)
Ubiquinone can take up two electrons and two protons upon reduction and serves as essential redox cofactor in several proteins. Out of its 9 possible redox states, only Q and Q– are seen in the QA site and Q, Q– and QH2 in the Q8 site of the reaction center of photosynthetic bacterium Rhodobacter sphaeroides. The focus of our interest was the investigation of kinetic and energetic aspects of Q– stability in the Q8 binding site. Under physiological conditions, the semiquinone anion is very stable and it binds more tightly than Q or QH2. At high light intensity of continuous excitation, however, it binds poorly and favors release to the solution. We attribute the decrease of semiquinone affinity to conformational changes in the QB binding site upon repetitive and frequent charge separation (and subsequent very fast recombination) in the photochemically closed reaction center.